Financial literacy and financial decision-making at older ages - FONG, Joelle H. (Institutional Knowledge at Singapore Management University, 2021)
How well older households manage their wealth holdings is an important determinant of their financial security during retirement, yet little is known about their financial decision-making and how this relates to their financial literacy. Our paper fills this gap by measuring financial literacy among older persons in the Singapore Life Panel and examining its association with timely credit card debt repayment, stock market participation, and age-based investment risk diversification. Most older respondents understand interest compounding and inflation, but fewer than half know about risk diversification. Almost all older credit card holders pay off their balances in a timely manner, but only 40% hold stocks; fewer than 18% with $1000+ in assets hold portfolios consistent with age-appropriate investment glide paths. We further show that a one-unit higher financial literacy score is associated with a greater propensity to timely pay off credit card balances (1.5 ppts), to hold stock (8.3 ppts), and to follow an age-appropriate investment glide path (1.7 ppts).